2023
DOI: 10.3390/foods12112219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quality of Canola Grains and Their Implications for Grain-Based Foods

Abstract: Canola, Brassica napus L., is a major oilseed crop that has various uses in the food, feed, and industrial sectors. It is one of the most widely produced and consumed oilseeds in the world because of its high oil content and favorable fatty acid composition. Canola grains and their derived products, such as canola oil, meal, flour, and bakery products, have a high potential for food applications as they offer various nutritional and functional benefits. However, they are affected by various factors during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…Regardless of the location, test weight increased significantly with increasing N application rates from 58.1 kg hL −1 in the control to a maximum of 60.3 kg hL −1 at 135 kg N ha −1 (Table 5). However, at the highest N rate of 168 kg N ha −1 , the test weight decreased to 59.5 kg hL −1 , which may be due to the increased lodging capacity of the plants (Sabbahi et al, 2023). Wu and Ma (2016) revealed that lodging had a significant correlation with the formation of seed size and biomass production in canola.…”
Section: Test Weightmentioning
confidence: 96%
“…Regardless of the location, test weight increased significantly with increasing N application rates from 58.1 kg hL −1 in the control to a maximum of 60.3 kg hL −1 at 135 kg N ha −1 (Table 5). However, at the highest N rate of 168 kg N ha −1 , the test weight decreased to 59.5 kg hL −1 , which may be due to the increased lodging capacity of the plants (Sabbahi et al, 2023). Wu and Ma (2016) revealed that lodging had a significant correlation with the formation of seed size and biomass production in canola.…”
Section: Test Weightmentioning
confidence: 96%
“…For instance, rapeseed historically contained high levels of unhealthy erucic acid. By utilizing a naturally occurring mutant FA elongase to convert oleic acid into erucic acid, Canadian breeders created new rapeseed varieties (referred to as "Canola") with 60-65% oleic acid and very low levels of erucic acid within a decade (Sabbahi et al, 2023). The same approach has been applied to develop high-oleic (60-75%) sunflower plants.…”
Section: Modifying the Composition Of Vegetable Oils For Industrial A...mentioning
confidence: 99%
“…Rapeseed is one of the most vital oil-seed crops that supply consumption products such as meal protein for humans and animal feed ( Sabbahi et al, 2023 ). Salinity stress impacts rapeseed yield by reducing seed germination, seedling growth and development, plant vigor, grain yield, and quality of the rapeseed ( Borchers & Pieler, 2010 ).…”
Section: Introductionmentioning
confidence: 99%